Evolution of the YABBY gene family in seed plants. Issue 2 (13th January 2016) - Finet, Cédric; Floyd, Sandra K.; Conway, Stephanie J.; Zhong, Bojian; Scutt, Charles P.; Bowman, John L.
SUMMARY: Members of the YABBY gene family of transcription factors in angiosperms have been shown to be involved in the initiation of outgrowth of the lamina, the maintenance of polarity, and establishment of the leaf margin. Although most of the dorsal‐ventral polarity genes in seed plants have homologs in non‐spermatophyte lineages, the presence of YABBY genes is restricted to seed plants. To gain insight into the origin and diversification of this gene family, we reconstructed the evolutionary history of YABBY gene lineages in seed plants. Our findings suggest that either one or two YABBY genes were present in the last common ancestor of extant seed plants. We also examined the expression of YABBY genes in the gymnosperms Ephedra distachya (Gnetales), Ginkgo biloba (Ginkgoales), and Pseudotsuga menziesii (Coniferales). Our data indicate that some YABBY genes are expressed in a polar (abaxial) manner in leaves and female cones in gymnosperms. We propose that YABBY genes already acted as polarity genes in the last common ancestor of extant seed plants.